DETERMINATION OF THE EFFICIENCY OF APPLICATION OF PACKAGES OF TEXTILE MATERIALS FOR THE PRODUCTION OF A SPECIAL PURPOSE JACKET - HARANINA, Olha; RED’KO, Yana; KAMENETS, Serhiy; VATAN, Raisa (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The results of research into the properties of modern textile materials, in particular, insulating materials, are presented for choosing a package of textile materials that will be the most effective in terms of quality for the production of a special-purpose jacket that will be used in low-temperature conditions. As insulating materials for the study of consumer properties of textile material packages, the material "Tinsulet", batting and sintepon, upper fabric "Oxford", lining fabric "Nylon" were used. Both the materials themselves and the packages of textile materials from the top fabric "Oxford", insulation material and lining fabric "Nylon" were studied. It is assumed that the choice of insulating material is among the presented assortment on the market of Ukraine. It was established that the most effective package is the package using the insulating material "Tinsulet". This package is characterized by the highest indicators of breaking load and air permeability, as well as the lowest surface density. All tested materials meet the requirements specified in DSTU EN 14058:2008. Today it is becoming relevant to study and compare the properties of the insulation material "Tinsuleit" with the materials of batting and sintepon, which are actively used by manufacturers in Ukraine. Therefore, it became necessary to compare the performance of one of the most modern insulating materials, "Tinsuleit", with batting, which has been used for about a hundred years, but which is almost gone in Europe and the USA. Rational results, which testify to the absolute superiority of the insulation material "Tinsuleit", were provided when evaluating the indicators of breaking load, air permeability, surface density of the insulation materials "Tinsuleit", sintepon, batting, top fabric "Oxford" and lining fabric "Nylon" separately and in composition of packages of textile materials. Therefore, in the case of replacement in the production of special clothing, insulation materials of batting and sintepon with "Tinsuleit" during the production in Ukraine, the term of use of special clothing will be significantly increased due to the improvement of strength properties, and the economic efficiency of its use will significantly improve. Increasing breathability and reducing the weight of clothing will provide opportunities for longer stay in low temperature conditions and have greater mobility and mobility of the consumer, thanks to which the demand for this special clothing will only grow.
Keywords: thinsulate; breathability; breaking load; packages of textile materials